Kinerja dan Kapasitas Struktur Bangunan Eksisting sesuai Prinsip Evaluasi ASCE 41-17 - Shinta Berlinda Wulandari; Hanie Teki Tjendani; Buntara Sthenly Gan (Magister Teknik Sipil, Fakultas Teknik, Universitas 17 Agustus 1945 Surabaya, 2026)
Indonesia is located in a highly active seismic region due to its position along the Pacific Ring of Fire, causing many existing buildings to remain vulnerable to earthquake loads, particularly structures designed using outdated seismic codes. This study aims to evaluate the performance and structural capacity of an existing reinforced concrete building based on the performance-based evaluation principles of ASCE 41-17 integrated with SNI 1726:2019 and SNI 2847:2019. The research employed a quantitative analytical method using numerical simulation through Tier 1 – Screening Procedure and Tier 3 – Systematic Procedure. Structural performance evaluation was conducted using nonlinear static pushover analysis to determine capacity curves, plastic hinge formation, drift behavior, and structural performance levels. The results indicate that the existing structure still contains several structural deficiencies, particularly in columns and lateral force-resisting systems. The pushover analysis shows that the structure is still capable of resisting moderate earthquake demands; however, its capacity and ductility decrease significantly under higher seismic intensity. The structure does not fully satisfy the Immediate Occupancy (IO) and Life Safety (LS) performance levels, although under certain conditions it still achieves Collapse Prevention (CP). Plastic hinge distribution concentrated in column elements indicates that the strong column–weak beam mechanism has not been achieved optimally, making columns the critical elements controlling global structural stability. Overall, the ASCE 41-17 performance-based evaluation approach proves effective in assessing the seismic performance and capacity of existing buildings and can serve as a basis for determining structural strengthening or retrofit requirements.